PRESSURES EXERTED BY COMMERCIALLY AVAILABLE LOWER LIMB COMPRESSION GARMENTS. Issue 7 (11th March 2014) - Hill, J; Howatson, G; van Someren, K; Davidson, S; Pedlar, C
Abstract : Background: Commercially available compression garments (CGs) enhance recovery from exercise in some, but not all studies. It has been suggested that the minimum physiologically effective pressure is 17.3 mmHg at the lower leg decreasing to 15.1 mmHg at the thigh (Watanuki and Murata, 1994). CGs are usually fitted using a generalised sizing system based on height and mass, potentially causing variability in the pressure exerted by the garment. Objective: We aimed to quantify the pressure, and the variability in pressure, exerted on the leg by CGs fitted according to the manufacturers instructions. Participants: 50 healthy, physically active individuals (n=26 male, n=24 female; age 18–65years) volunteered to participate. Design: Participants were fitted with CGs according to manufacturers guidelines. The compressive force of the garments was measured in participants standing in the anatomical position including: the medial aspect of the calf at the site of maximal girth and at the midpoint of the femur measured between the inguinal crease and the superior aspect of the patella, of the lower limb. Data were compared to target pressure values. Results: Pressure fell short of target values by 3% and 20% at the calf and by 34% and 47% at the thigh for males and females respectivelyFigure 1 . Conclusion: Many individuals may not be experiencing an adequate pressure from CG (Figure 1); this might explain the inconsistency within the literature regarding CG and recovery. Future research should measure and control for actual pressure exerted by the garment.